2020
DOI: 10.1177/1558925020978651
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of functional biomolecules onto polypropylene fabric using plasma pre-treatment

Abstract: In order to realize the immobilization of collagen, chitosan and sericin on the surface of polypropylene fabric, the fabric is treated by ammonia and nitrogen low temperature plasma to produce reactive groups, and then the epoxy compounds (ethylene glycol diglycidyl ether, trimethylolpropane triglycidyl ether) are used as crosslinkers for a bridging process. Single factor experiment is carried out to investigate the influence of crosslinking parameters (temperature, time and the dosage of crosslinker) on immob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The spectra of the N 2 plasma-irradiated polypropylene fabric showed two new bands at 3341 cm −1 and 1649 cm −1 which belong to the N–H stretching and bending vibrations of the –NH 2 induced into the fabric structure after being irradiated with N 2 plasma beam. Ma et al confirmed that about 2%–10% NH 2 /N is generated upon exposure of polypropylene fabric to N 2 plasma beam, 45 which explains the low intensity of the N–H stretching vibration band at 3339 cm −1 . Similar to the FTIR spectra of O 2 plasma/sericin-treated PP fabric, N 2 plasma/sericin-treated PP shows typical spectra of the amide I, II, and III bands at 1640 cm −1 , 1530 cm −1 , and 1230 cm −1 of proteins.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The spectra of the N 2 plasma-irradiated polypropylene fabric showed two new bands at 3341 cm −1 and 1649 cm −1 which belong to the N–H stretching and bending vibrations of the –NH 2 induced into the fabric structure after being irradiated with N 2 plasma beam. Ma et al confirmed that about 2%–10% NH 2 /N is generated upon exposure of polypropylene fabric to N 2 plasma beam, 45 which explains the low intensity of the N–H stretching vibration band at 3339 cm −1 . Similar to the FTIR spectra of O 2 plasma/sericin-treated PP fabric, N 2 plasma/sericin-treated PP shows typical spectra of the amide I, II, and III bands at 1640 cm −1 , 1530 cm −1 , and 1230 cm −1 of proteins.…”
Section: Resultsmentioning
confidence: 98%
“…1 Polypropylene (PP) is an important element in many applications because of its versatile properties, such as excellent tensile properties, abrasion resistance, resiliency, and resistance to most chemicals and solvents. 2 However, PP also has some inadequacies that need to be addressed before usage in the clothing industry. One of the most significant disadvantages of PP is its deterioration under the influence of ultraviolet radiation, which can cause the material to become brittle and lose its strength over time.…”
Section: Introductionmentioning
confidence: 99%
“…The more O-containing groups produced on the PP surface after O 2 plasma pretreatment [23,46], the more favorable polyol post-grafting is. Hence, it is necessary to optimise the plasma treatment of PP fiber.…”
Section: Pp Fabric After Plasma Treatmentmentioning
confidence: 99%
“…Wu et al [22] introduced a modification of polypropylene treated by air plasma and feather keratin graft, the results of which showed that the surface hydrophilicity and printing property were greatly improved. Ma et al [23] achieved three hydrophilic biomolecule grafting onto PP fabric using NH 3 and N 2 low temperature plasma pre-treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Crosslinking of gelatin with glycerol epoxy resin to form a hyperbranched polymer was shown to reduce its brittleness and increase water resistance [ 30 ]. 1,1,1-triglycidyltrimethylolpropane ( Scheme 1 , structure 3) was applied to improve the mechanical properties of chitosan beads precipitated in alkaline solution [ 31 ], fabricate chitosan nanofiltration membranes [ 32 ], and graft chitosan to the plasma-treated polypropylene fabric [ 33 ]. In all cases, reactions proceeded at room or elevated temperature, and the advantage of triglycidyl over diglycidyl ethers was not always unquestionable due to the higher probability of self-cross-linking reaction at high concentration of triglycidyl ethers [ 33 ].…”
Section: Introductionmentioning
confidence: 99%